Clinicopathologic and Molecular Characterization of Epstein-Barr Virus–positive Plasmacytoma. (1st October 2022) - Zhou, Ting; Cheng, Jinjun; Karrs, Jeremiah; Davies-Hill, Theresa; Pack, Svetlana D.; Xi, Liqiang; Tyagi, Manoj; Kim, Jung; Jaffe, Elaine S.; Raffeld, Mark; Pittaluga, Stefania
Abstract : Epstein-Barr virus (EBV)-positive plasmacytoma is a rare plasma cell neoplasm. It remains unclear whether EBV-positive plasmacytoma represents a distinct entity or a variant of plasmacytoma. It shares morphologic features with plasmablastic lymphoma (PBL) and may cause diagnostic uncertainty. To better understand EBV-positive plasmacytoma and explore diagnostic criteria, this study describes 19 cases of EBV-positive plasmacytoma, compared with 27 cases of EBV-negative plasmacytoma and 48 cases of EBV-positive PBL. We reviewed the clinicopathologic findings and performed immunohistochemistry, in situ hybridization for EBV, fluorescence in situ hybridization for MYC, and next-generation sequencing. We found that 63.2% of patients with EBV-positive plasmacytoma were immunocompromised. Anaplastic features were observed in 7/19 cases. MYC rearrangement was found in 25.0% of them, and extra copies of MYC in 81.3%. EBV-positive and EBV-negative plasmacytomas possessed similar clinicopathologic features, except more frequent cytologic atypia, bone involvement and MYC aberrations in the former group. The survival rate of patients with EBV-positive plasmacytoma was comparable to that of patients with EBV-negative plasmacytoma. In comparison to PBL, EBV-positive plasmacytoma is less commonly associated with a "starry-sky" appearance, necrosis, absence of light chain expression, and a high Ki67 index (>75%). The most recurrently mutated genes/signaling pathways in EBV-positive plasmacytoma are epigenetic regulators, MAPK pathway, and DNA damage response, while the most frequently reported mutations in PBL are not observed. Collectively, EBV-positive plasmacytoma should be regarded as a biological variant of plasmacytoma. Thorough morphologic examination remains the cornerstone for distinguishing EBV-positive plasmacytoma and PBL, and molecular studies can be a valuable complementary tool.